2010
DOI: 10.1097/scs.0b013e3181f4040a
|View full text |Cite
|
Sign up to set email alerts
|

Serum Paraoxonase Activity and Oxidative DNA Damage in Patients With Laryngeal Squamous Cell Carcinoma

Abstract: We conclude that, in patients with laryngeal squamous cell carcinoma, the oxidant/antioxidant balance was impaired in favor of lipid peroxidation and DNA damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Previous studies have reported associations between PON1 genetic polymorphisms or PON1 enzyme activity and oxidative stress, but the results are still inconclusive. Serum PON1 activity has been negatively correlated with urinary 8-OHdG levels in patients with Alzheimer’s disease [ 39 ] and laryngeal squamous cell carcinoma [ 40 ]. Bhattacharyya et al found that the PON1 192 RR genotype was associated with a lower level of oxidative stress [ 13 ], and Ji et al similarly reported that carriers of the PON1 rs662 Q allele have a significantly higher level of 8-OHdG in sperm DNA than R allele carriers [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported associations between PON1 genetic polymorphisms or PON1 enzyme activity and oxidative stress, but the results are still inconclusive. Serum PON1 activity has been negatively correlated with urinary 8-OHdG levels in patients with Alzheimer’s disease [ 39 ] and laryngeal squamous cell carcinoma [ 40 ]. Bhattacharyya et al found that the PON1 192 RR genotype was associated with a lower level of oxidative stress [ 13 ], and Ji et al similarly reported that carriers of the PON1 rs662 Q allele have a significantly higher level of 8-OHdG in sperm DNA than R allele carriers [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that PON1 activity reduces the risk of cardiovascular disease caused by oxidative stress (14). Besides, PON1 activity reduces inflammatory processes, hyperthyroidism, certain neuropathies, diabetes, cancer, and many other diseases, by preventing oxidative stress (15)(16)(17)(18)(19)(20). For instance, Malik et al (4) report that the role of oxidative imbalance in the oral squamous cell carcinoma may be associated with the antioxidant status.…”
mentioning
confidence: 99%
“…16 Bansal et al reported that low PON1 activity may be considered as additional risk factor for development of vascular complications in type 2 diabetes mellitus. 17 Previous studies also suggested that low PON1 activity was associated with an increased risk for many cancer types, such as lung cancer, 21 laryngeal squamous cell carcinoma, 22 gastric 23 and pancreatic cancers. 24 Our results are supported by these previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…18 In recent years, number of the studies investigating the relation between PON1 activity and cancer are increasing. Compared to the healthy controls, lower serum levels of PON1 were measured in patients suffering from breast 19,20 , lung 20,21 , laryngeal 22 , gastric 23 , pancreatic 24 and colorectal cancer. 20 Variations due to the presence of single nucleotide polymorphisms in antioxidant enzymes may contribute to the inter-individual differences between the transcript levels and enzyme activities, which might play a significant role in the development of cancer.…”
Section: Introductionmentioning
confidence: 99%